Possibility of incorrect evaluation of intraoperative blood loss during open and laparoscopic distal pancreatectomy - Keisuke Toya; Yoshito Tomimaru; Shogo Kobayashi; Kazuki Sasaki; Yoshifumi Iwagami; Daisaku Yamada; Takehiro Noda; Hidenori Takahashi; Yuichiro Doki; Hidetoshi Eguchi (Annals of Gastroenterological Surgery)
Abstract Aim Decreasing intraoperative blood loss is one reported advantage of laparoscopic surgery compared with open surgery. However, several reports indicate that blood loss during laparoscopic surgery may be underestimated. No studies have evaluated this possibility in laparoscopic distal pancreatectomy (LDP). Here we evaluated estimated blood loss (e‐BL) compared to intraoperative blood loss (i‐BL) during distal pancreatectomy (DP). Methods This study included 114 patients undergoing DP in our institution during the study period. We examined the relationship between i‐BL and e‐BL. Based on these results, we further investigated the relationship with LDP. Results The laparoscopic approach was used in a significantly higher percentage of patients in e‐BL > i‐BL group compared to e‐BL < i‐BL group (55.9% vs 10.9%, p < 0.0001). Within the LDP group (n = 39), e‐BL was significantly more than i‐BL (388 ± 248 vs 127 ± 160 mL; p < 0.0001). Within the open distal pancreatectomy (ODP) group (n = 75), e‐BL was significantly less than i‐BL (168 ± 324 vs 281 ± 209 mL; p = 0.0017). The e‐BL > i‐BL trend in the LDP group was consistent, regardless of the indication for DP. In contrast, the finding of i‐BL > e‐BL in the ODP group was limited to patients with pancreatic cancer. Conclusion During LDP, e‐BL was significantly more than i‐BL. During ODP, e‐BL was significantly less than i‐BL, only in patients with pancreatic cancer. These results suggested the possibility of i‐BL underestimation during LDP, and overestimation during ODP in cases with pancreatic cancer.